Сравнительное изучение анатомического строения листьев Phlox sibirica L. и Phlox sibirica var. borealis (Wherry) B. Boivin - Бутенкова; Алина Николаевна; Беляева; Татьяна Николаевна (биолог) (Acta Biologica Sibirica, 2019)
In this comparative research of the leaf anatomy of Phlox sibirica and Phlox sibirica var. borealis we discovered that morphometric features of the leaf blades structure in 95 % of cases significantly differ at a significance level of P < 0.05. Statistically significant differences were not found only in determining the stomatal index the value of which also corresponds to other types of groundcover phlox. The studied taxa are characterized by collateral vascular bundles an anomocytic type of the stomatal apparatus and elongated winding epidermal cells. Phlox sibirica is distinguished by a better development of collenchyma strands which provides sheet rigidity even with the loss of turgor xylem and the most photosynthetically active layer of mesophyll (cells of the upper layer). Thus in the anatomical structure of the studied phloxes the features characteristic of xerophytic-heliophytic species more pronounced in Phlox sibirica were revealed. The leaf anatomy of the studied taxa reflects their adaptation to conditions with an unfavorable water regime (ensures the maintenance of a normal water balance) and excessive lighting.